Influência do envelhecimento na concentração de ácido hialurônico nas pregas vocais de ratas fêmeas - Ramos, Hugo Valter Lisboa [UNIFESP] (2012)
The vibration of the vocal fold lamina propria is an important factor involved in vocal production and aging may change the amount of hyaluronic acid in the vocal fold leading to dysphonia. AIMS: This study compares the concentration of hyaluronic acid in vocal folds of aged and young female rats. Study design: experimental. MATERIALS AND METHODS: We used the vocal cords of 13 female rats divided into two groups: five aged rats and eight young ones. The tissue concentration of hyaluronic acid was determined using the fluorimetric method with the hyaluronic acid binding-protein coated on plates of enzyme-linked immunosorbent assay (ELISA), conjugated with biotin. Europium-labeled streptavidin was added and, after europium release with the use of enhancement solution, the final fluorescence was measured in a fluorometer. RESULTS: We found the following concentrations of hyaluronic acid in vocal fold according to the group: 581.7 ng/mg in old female rats and 1275.6 ng/mg in young female rats. Statistical analysis showed differences between groups. CONCLUSIONS: The vocal folds of old female rats have a lower concentration of hyaluronic acid when compared to such concentration on the vocal folds of young female rats.